Electrophoretic analysis of the Cordylus cordylus species group (Sauria: Cordylidae) in the southwestern Cape Province, South Africa - Brody, Larisa Susanna (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1991.